1989
DOI: 10.1016/0014-5793(89)81778-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of cDNA for precursor of a crustacean hyperglycemic hormone

Abstract: Crustacean hyperglycemic hormone (CHH) from Curcinus maenus, a 72 amino acid neuropeptide, originates in neurosecretory perikarya in the eyestalk ganglia. Poly (A)RNA was isolated from these perikarya and a cDNA library was prepared. Screening of 20000 clones with a 26-mer oligonucleotide, corresponding to a partial sequence of CHH, yielded one positive clone with an insert of approximately 2000 bp, which contained the complete coding sequence for a pre-pro CHH. This precursor consists of a putative 26 amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Before this study, only two crustacean brain-gut peptides had been identified: crustacean hyperglycemic hormone and crustacean hyperglycemic hormone precursor-related peptide, both of which are found in the nervous system and in the foregut and midgut of the crab C. maenas (Kegel et al, 1989;Weidemann et al, 1989;Tensen et al, 1991;Chung et al, 1999;Webster et al, 2000;Dircksen et al, 2001). Our identification of Gly 1 -SIFamide and CabTRP Ia in the Cancer midgut now brings to four the number of fully characterized brain-gut peptides in decapod species, and suggests the possibility that there may be a myriad of such peptides in the midgut epithelium of decapod crustaceans, as there are in insects.…”
Section: Brain-gut Peptides In Crustacea: Rule or Exception?mentioning
confidence: 99%
“…Before this study, only two crustacean brain-gut peptides had been identified: crustacean hyperglycemic hormone and crustacean hyperglycemic hormone precursor-related peptide, both of which are found in the nervous system and in the foregut and midgut of the crab C. maenas (Kegel et al, 1989;Weidemann et al, 1989;Tensen et al, 1991;Chung et al, 1999;Webster et al, 2000;Dircksen et al, 2001). Our identification of Gly 1 -SIFamide and CabTRP Ia in the Cancer midgut now brings to four the number of fully characterized brain-gut peptides in decapod species, and suggests the possibility that there may be a myriad of such peptides in the midgut epithelium of decapod crustaceans, as there are in insects.…”
Section: Brain-gut Peptides In Crustacea: Rule or Exception?mentioning
confidence: 99%
“…Both peptides share 28% of identical amino acid residues. The cDNA structure of the CHH precursor has previously been established in our laboratory [9]. Comparison of CHH and MIH precursors reveals striking and interesting differences.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm this, it would be highly interesting to know the structure of the VIH precursor. Although CHH precursors other than that of Carcinus [9] have not yet been published, there is indirect evidence that they share structural characteristics, in particular the presence of CPRPs. Such peptides have been isolated and sequenced from the sinus glands of four species [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations